Financial management and accounting in the public sector - Bandy, Gary (New York, NY : Routledge, 2023)
"The importance of public financial management for the health and wellbeing of citizens became dramatically apparent as governments sought to respond to the coronavirus pandemic in 2020. Now, governments and other public sector organizations face the challenge of recovering from the pandemic whilst also seeking to achieve. Sustainable Development Goals, with squeezed budgets and ever-increasing demands for public services. Public sector managers are confronted daily with targets and demands that are often set in confusing accounting and financial language. In Financial Management and Accounting in the Public Sector, Gary Bandy employs a clear and concise narrative to introduce the core concepts of public financial management to help those managers to deliver programmes, projects and services that are value for money. As the author puts it, managing public money is an art, not a science. This third edition has been revised and updated throughout, offering: A structure that is more clearly linked to the stages of the public financial management cycle Greater coverage of transparency and accountability issues A broader view of public procurement to include goods, works and services and effective contract management An increased focus on public spending in the context of a post-COVID environment With a glossary of terms to help managers understand and be understood by accountants, as well as learning objectives, discussion questions and exercises, this practical textbook will help students of public management and administration to understand the financial and accounting aspects of managing public services"--
Revised edition of the author's Financial management and accounting in the public sector, 2015.
OCLC-licensed vendor bibliographic record.
Keywords: Finance, Public; Public administration; Finance, Public -- Accounting; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Accounting / Managerial; BUSINESS & ECONOMICS / Budgeting